When Princesses Become Dragons: Critical Literacy, Damsel, and Confronting Rape Culture in English Classrooms. Issue 3 (1st December 2021) - Boehm, Shelby; Colantonio-Yurko, Kathleen; Olmstead, Kathleen; Miller, Henry "Cody"
Abstract: In this article we offer curricular suggestions for teaching Elana K. Arnold's young adult title Damsel, a subverted fairytale rewrite, using a critical literacy framework. In doing so, we outline how English curriculum has often upheld oppressive systems that harm women, and how our teaching can challenge such systems. We situate this work through the retelling of a fairytale trope given the ubiquity of such stories in secondary students' lives. Our writings have teaching implications for both secondary English language arts classrooms and higher education fields such as English, folklore, mythology, and gender studies. We end by noting the limitations of such teaching.